2014 IEEE Symposium on 3D User Interfaces (3DUI) 2014
DOI: 10.1109/3dui.2014.6798845
|View full text |Cite
|
Sign up to set email alerts
|

Feet movement in desktop 3D interaction

Abstract: In this paper we present an exploratory work on the use of foot movements to support fundamental 3D interaction tasks. Depth cameras such as the Microsoft Kinect are now able to track users' motion unobtrusively, making it possible to draw on the spatial context of gestures and movements to control 3D UIs. Whereas multitouch and mid-air hand gestures have been explored extensively for this purpose, little work has looked at how the same can be accomplished with the feet. We describe the interaction space of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…In summary, (1) we built 1D and 2D ISO 9241-9 compliant movement time models for unconstrained foot pointing; (2) we found that unconstrained foot pointing is considerably slower than mouse pointing, but comparable to other input devices such as joysticks and touchpads; (3) we found no significant difference in performance between the dominant and non-dominant foot; (4) we found that left and right movement is easier than backwards and forwards; (5) the most comfortable movement for desktop foot interaction is heel rotation; (6) techniques that have a direct spatial mapping to the representation outperform the others; (7) when variables are shown separately, two feet work better than one; (8) we show that the feet perform similarly to the scroll wheel in tasks where the feet are used in conjunction with the mouse; and (9) we provide design guidelines and considerations based on our findings.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…In summary, (1) we built 1D and 2D ISO 9241-9 compliant movement time models for unconstrained foot pointing; (2) we found that unconstrained foot pointing is considerably slower than mouse pointing, but comparable to other input devices such as joysticks and touchpads; (3) we found no significant difference in performance between the dominant and non-dominant foot; (4) we found that left and right movement is easier than backwards and forwards; (5) the most comfortable movement for desktop foot interaction is heel rotation; (6) techniques that have a direct spatial mapping to the representation outperform the others; (7) when variables are shown separately, two feet work better than one; (8) we show that the feet perform similarly to the scroll wheel in tasks where the feet are used in conjunction with the mouse; and (9) we provide design guidelines and considerations based on our findings.…”
Section: Introductionmentioning
confidence: 80%
“…Sensing may be performed by conventional colour cameras [13], depth cameras [4,16], optical motion capture [18], audio [15] and smart floors [2].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations